2017
DOI: 10.1007/s00227-017-3255-1
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale movements in the oceanic environment identify important foraging areas for loggerheads in central Mediterranean Sea

Abstract: Loggerhead sea turtles (Caretta caretta) are known to display a wide range of movement patterns during the different stages of their life cycle, but empirical information to document this extensive behavioural plasticity is still limited. This is especially true for large, adultsized individuals, that are thought to mainly forage in neritic areas. In the present paper, eight adult-sized loggerhead turtles were tracked using satellite telemetry to identify the location of their foraging grounds in the seas alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 60 publications
(81 reference statements)
4
22
0
Order By: Relevance
“…In the Tyrrhenian Sea, juveniles and adult-sized turtles foraging on pelagic prey frequent the oceanic waters around the Aeolian Archipelago, north of Sicily (Blasi & Mattei 2017). Moreover, a recent satellite-tracking study has revealed a high use area in the southern Tyrrhenian Sea (Luschi et al 2018), so this basin may be of importance for loggerhead turtles foraging in the oceanic realm. Other areas where satellite-tracked turtles have taken up residence, presumably for foraging, are the Algerian Sea (Hays et al 2014a), the deep waters of the Sicilian Strait (Bentivegna 2002, Casale et al 2012c, the western Ionian (Mingozzi et al 2016) and the central Ionian (Zbinden et al 2008.…”
Section: Oceanic Foraging Areasmentioning
confidence: 99%
“…In the Tyrrhenian Sea, juveniles and adult-sized turtles foraging on pelagic prey frequent the oceanic waters around the Aeolian Archipelago, north of Sicily (Blasi & Mattei 2017). Moreover, a recent satellite-tracking study has revealed a high use area in the southern Tyrrhenian Sea (Luschi et al 2018), so this basin may be of importance for loggerhead turtles foraging in the oceanic realm. Other areas where satellite-tracked turtles have taken up residence, presumably for foraging, are the Algerian Sea (Hays et al 2014a), the deep waters of the Sicilian Strait (Bentivegna 2002, Casale et al 2012c, the western Ionian (Mingozzi et al 2016) and the central Ionian (Zbinden et al 2008.…”
Section: Oceanic Foraging Areasmentioning
confidence: 99%
“…The higher SPUE of the southern Tyrrhenian Sea compared to that of the Adriatic Sea was rather unexpected, since the Tyrrhenian Sea has thus far not received much consideration as an important marine habitat (see also Casale & Mariani 2014 for a discussion on this topic). Only recently, Luschi et al (2018) identified a high-use area in the north-central Tyrrhenian, derived from satellite tracking results on 8 adult-sized loggerhead turtles. Our results could not confirm this finding, because no effort was made through this part of the Tyrrhenian Sea.…”
Section: Sea Turtle Distributionmentioning
confidence: 99%
“…In brief, while loggerhead turtles and especially their juveniles can be found in virtually all oceanic areas in the Mediterranean Sea, data derived from fishery by-catch rates indicate relatively high abundances in the westernmost part of the basin, the southern Sicily Channel, and the northern Ionian/southern Adriatic Sea (Casale et al 2018). In the Tyrrhenian Sea, catch rates are lower, but nonetheless, recent studies have also highlighted the Tyrrhenian Sea as an important oceanic area for this species (Blasi & Mattei 2017, Luschi et al 2018. Unfortunately, no comparable by-catch rates are available for other areas in the eastern Mediterranean, although high turtle abundances could be expected there because of the proximity of its oceanic areas to known nesting beaches (Casale et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although some behavioural similarities can be observed between individuals from the same species, a wide variation in plasticity responses is commonly evidenced in sea turtles [25][26][27][28][29][30][31][32], and is revealed by contrasting diet [33][34][35], diving behaviour [25,26], spatial dynamics [20,28,31] or habitat used [25,36]. For example, adult female green, loggerhead and leatherback turtles explore different habitats during their postnesting migration, using both neritic and oceanic environments [27,31,37]. Similarly, juvenile green turtles from the Atlantic spread in different directions to reach distinct foraging grounds [32].…”
Section: Introductionmentioning
confidence: 99%